Phytochemical Studies on Glinus oppositifolius (L.) Aug. DC. - Chhanda, Sadia Afrin; Muslim, Tanvir; Rahman, Md Aziziur (Dhaka University Journal of Science, 2015)
The compounds dotriacontyl docosanoate and trilinolein have been isolated from petroleum ether extract and ethyl acetate extract, respectively of the plant Glinus oppositifolius (L.) Aug. DC. The compounds were characterised by spectroscopic techniques. Total vitamin C content has been estimated and fatty acid composition has been analysed by GLC. DOI: http://dx.doi.org/10.3329/dujs.v62i1.21960 Dhaka Univ. J. Sci. 62(1): 45-48, 2014 (January)